Avaliação da via pró-resolutiva envolvendo a proteína anexina A1 e seu receptor FPR-2 no contexto da pneumonia bacteriana experimental. - Edvaldo Souza Lara (2023)
Pneumonia represents one of the main causes of morbidity and mortality worldwide. This pathology results from the infection of the lower respiratory tract by microorganisms such as viruses, fungi and mainly by Gram-positive or Gram-negative bacteria. Inflammation of the airways and lung parenchyma triggered during infection is essential and must be orchestrated spatially and temporally by cells and mediators of immune system, aiming to eliminate infectious stimuli and restore tissue homeostasis, protecting the host from the damage caused by the infection. Conversely, an inefficient engagement of the resolution inflammation program during lung infection leads to exacerbation inflammation, causing intense pulmonary damage and bacterial dissemination, increasing pneumonia severity. We have shown that the pro-resolving pathway engaged by the protein Annexin A1 (AnxA1) and its receptor FPR-2 control the inflammatory response and bacterial dissemination in experimental pneumonia induced by pneumococcus (a Gram-positive bacteria), and treatment of mice using the AnxA1 peptidomimetic AnxA1 Ac2-26, afford protection during pneumococcal pneumonia. However, the role of this pathway in infections caused by Gram-negative bacteria has not yet been assessed. Herein, we have evaluated the role of the AnxA1/FPR-2 axis in the inflammatory response caused by pneumonia induced by the Gram-negative bacterium Escherichia coli. For that, wild-type (WT) and Annexin A1-deficient (AnxA1 KO) or FPR2/3 (FPR-2/3 KO) mice were infected with E. coli (ATCC 25922) and euthanized after 24 hours for evaluation of inflammatory parameters and lung bacterial load. In separate experiments, WT animals infected with E. coli were treated 8h after infection with Ac2-26 and euthanized 24h after infection for evaluation of the same parameters. Our results show that AnxA1 KO animals infected with E. coli, when compared to the WT group, showed a marked inflammatory response, characterized by a greater neutrophilic infiltrate in the airways and a smaller number of macrophages, associated with lower apoptosis/efferocytosis counts and a higher bacterial load in the lungs. The greater neutrophilic infiltrate in AnxA1 KO animals was accompanied by higher levels of pro-inflammatory cytokines and more intense lung damage. Similarly, FPR-2/3 KO animals showed a more exacerbated inflammatory response profile, with greater lung damage and higher lethality associated with E. coli infection, when compared to WT animals. Interestingly, E. coli- infected mice treated with Ac2-26 show reduced neutrophilic infiltration and increased number of macrophages, associated with higher apoptosis/efferocytosis counts and a decreased bacterial load in the airways and lungs. Furthermore, treatment with Ac2-26 decreases pro-inflammatory cytokines and lung damage associated with infection. In summary, the engagement of the AnxA1/FPR-2 axis is an important mechanism for inflammation resolution and bacterial clearance during pneumonia caused by E. coli. The Anxa1 peptidomimetic Ac2-26 was effective this pre-clinical infectious model and can constitute a new adjunctive therapeutic strategy for the treatment of infectious lung diseases.